Essential Oils against Candida auris-A Promising Approach for Antifungal Activity - Adam Kowalczyk (MDPI AG, 2024)
The emergence of Candida auris as a multidrug-resistant fungal pathogen represents a significant global health challenge, especially given the growing issue of antifungal drug resistance. This review aims to illuminate the potential of essential oils (EOs), which are volatile plant secretions containing complex mixtures of chemicals, as alternative antifungal agents to combat C. auris, thus combining traditional insights with contemporary scientific findings to address this critical health issue. A systematic literature review was conducted using the PubMed, Scopus, and Web of Science databases from 2019 to 2024, and using the Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) protocol to identify relevant studies on the antifungal efficacy of EOs or their components against C. auris. Of the 90 articles identified, 16 were selected for detailed review. The findings highlight the diverse mechanisms of action of EOs and their components, such as disrupting fungal cell membranes, inducing the production of reactive oxygen species (ROS), and impeding biofilm formation, suggesting that some of them may be as effective as, or better than, traditional antifungal drugs while potentially limiting the development of resistance. However, issues such as variability in the composition of EOs and a paucity of clinical trials have been identified as significant obstacles. In conclusion, EOs and their active ingredients are emerging as viable candidates for creating effective treatments for C. auris, underscoring their importance as alternative or complementary antifungal agents in the face of increasing drug resistance. The call for future research underscores the need for clinical trials and standardization to unlock the full antifungal potential of EOs against C. auris.